Reog Sebagai Medium Harmoni - Zuhriyah, Nunik (Proceedings of Annual Conference for Muslim Scholars, 2025)
This study aims to examine the values of love and tolerance contained in the Reog Ponorogo tradition and its relevance to the perspective of Islamic knowledge. Reog as a local cultural heritage, not only functions as a performing art, but also as a medium of social harmony that unites various levels of society regardless of religious or cultural backgrounds. Through a qualitative approach using case study, this research collected data through observation, interviews, and literature review related to the Reog tradition and social practices of the Ponorogo community. The results of the study show that the values of togetherness, mutual respect, and cooperation in Reog performances are in line with the principles of love and tolerance (tasamuh) in Islamic teachings. The integration of Ponorogo's local wisdom with Islamic knowledge can be a model of global harmony rooted in tradition, while also contributing significantly to the development of a peaceful civilization.